Outcome of Operative Treatment of Displaced Midshaft Clavicle Fracture Compared With Conservative Treatment (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Clavicles fracture accounts for 2.6%–5% of adult fractures. Fractures in the middle-third represent 69%–82% of all clavicle fractures.This prospective comparative study was done to evaluate the effectiveness of treatment options of conservative and operative method by plate for displaced midshaft of clavicle fractures in adult. Materials and methods:  76 patients between 18 to 70 years of age with a displaced midshaft fracture of clavicle were enrolled in this study. They were randomized in two groups to be treated with either triangular sling or operative fixation by anatomical plate.We analyzed the outcome of both groups by standard clinical and radiological follow-up at least one year with DASH score. Results: Mean age in conservative group was 52.2±13.2 years and 32.1±9.3 years in operative group. There was male predominance in both groups 71.7% (54). Mean time to radiographic union was 19.9±3.2 weeks in conservative group and 14.9±2.7 weeks in operative group. The total complications were 26.3% where 2.6% (01) nonunion in the operative group compared with 13.2% (05) in the conservative group. At one year of follow up, operative group were more likely to be satisfied with clinical and radiological outcome than conservative group by DASH score. Conclusions: Operative fixation of displaced mid shaft fracture of clavicle in adult showed improved functional outcome, faster return to daily activities and lower rate of complications compared with nonoperative treatment.JCMCTA 2019 ; 30 (1) : 21-26